Implementasi Kurikulum Merdeka Ditinjau Dari Projek Penguatan Profil Pelajar Pancasila ( P5 ) Tema Kebhinekaan Global Dengan Menggunakan Model Project Based Learning ( PjBL ) Di Sekolah Menengah Atas Negeri 6 Malang, ( Studi Deskripsi Di Sekolah Menengah - Natalia Aristina Dewi; Ifana Sari, Yuli; Ba’diya Kusufa, Roni Alim (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
Based on observations made by the author at SMA Negeri 6 Malang, it was found that the application and implementation of learning from the Pancasila Student Profile Strengthening Project (P5) in terms of the theme of Global Diversity using a project-based learning model for class X (Ten) students is seen as new, innovative and participatory . students are active in the learning process. So the authors are interested in conducting research. The purpose of this study was to determine the implementation of P5 on the theme of Global Diversity as the implementation of the Independent Curriculum and the implementation of P5 using a project-based learning model. The research method used is descriptive method with data collection tools in the form of documents, observations and interviews. The implementation of P5 as an implementation of the Independent Curriculum at SMA Negeri 6 Malang is a curriculum structure consisting of 2/3 intracurricular or face-to-face activities (KBM) and 1/3 co-curricular activities or P5 Projects. Designing the learning implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Global Diversity using the Project Based Learning learning model. The stages in its implementation are the stages of socialization, planning, monitoring in the form of holding action activities, holding celebrations, evaluating and reflecting. Each stage carried out in the learning implementation of the Pancasila Student Profile Strengthening Project (P5) uses the syntax in PjBL. The teacher as a facilitator is in charge of assisting, directing and providing input and suggestions for project implementation so that students are expected to develop according to their talents and interests. The conclusion from the implementation of P5 students is expected to be able to develop Pancasila student profiles and become agents of social change who are actively involved in solving social problems that exist in society. So that it can maximize its role as an important part of society and the state.